Design and Implementation of Digital Image Processing using STM32F407ZG Microcontroller for Traffic Light Management System - Achmad Muzahid; Inung Wijayanto (Proceeding of the Electrical Engineering Computer Science and Informatics, 2014)
Traffic jam is one of the big problems happened ina big city, such as Jakarta and Bandung. Sometimes the trafficjam is caused by the inappropriate traffic light time control. Thispaper describes the prototype implementation of traffic lightcontrol system by analyzing the image condition of the streetcaptured by camera. The digital signal processing algorithm andthe time of the traffic light are controlled by a STM32F407ZGMicrocontroller. The size of Random Access Memory (RAM) islimited, so an additional external RAM is used in this research.The system input is 120 x 160 pixels of road image which alreadystored in the SD Card. A digital signal processing is used todetermine which road has more traffic, and then the system willadjust the time of the traffic light based on the calculation.